SOSIALISASI TATA CARA PENDAFTARAN TANAH WAKAF DI MUI KABUPATEN SIMALUNGUN - Maria Rosalina; Az Zahra Zulfikar (Universitas Islam Sumatear Utara, 2023)
Waqf institutions are one of the Islamic social institutions that have high socio-economic value, and are a form of embodiment of social justice in Islam. in general, so it is necessary to develop its utilization in accordance with sharia principles, as mentioned in the Al-Qur'an surah At-Taubah verse 103. However, in reality many waqf lands are neglected in the community, giving rise to legal problems, especially in Simalungun Regency. This is due to Nazhir's inability to manage and develop waqf assets, the attitude of the people who do not care, the community does not understand the status of waqf assets that should be protected, and the community does not understand how to register waqf land. This problem encourages extension agents to cooperate with Ladui MUI Province, MUI Simalungun Regency, to conduct legal counseling entitled Procedures for Registration of Waqf Land in the form of Community Service at the Simalungun Regency MUI Office. Ways and conditions for registering waqf land, understanding the elements of waqf, nazhir waqf obligations, understanding legal issues regarding waqf and the legal force of waqf certificates. The conclusion in this activity is that it is necessary to increase the frequency and socialization regarding. Procedures for Waqf Land Registration.